Civilization and Capitalism15th-18th Century: The Structures of Everyday Life - Fernand Braudel; BRAUDEL (Fernand) (London William Collins Sons & Co. Ltd, 1979)
By examining in detail the material life of pre-industrial peoples around the world, Fernand Braudel significantly changed the way historians view their subject. Volume I describes food and drink, dress and housing, demography and family structure, energy and technology, money and credit, and the growth of towns.
Keywords: World Population; Social History; Economic History; Civilization